SAAF stakeholder co-design workshop in Thai Nguyen Province, Vietnam: Workshop report - Nguyen Thi Thinh; Atieno, Mary; Dao Thi Thu Hang; Sinh Dang-Xuan; Nguyen Thi Minh Phuong; Le Thi Thanh Huyen; Le Thi Huyen Trang; Nguyen Thi Thanh Ha; Nguyen Thi Thu Hien; Nguyen Thi Quynh Chi; Lo Quang Thanh; Unger, Fred; et al. (International Livestock Research Institute, 2025)
Sustainable Animal and Aquatic Foods (SAAF) is one of the eight CGIAR science programs for the 2025–2030 period, with the vision to improve the livelihoods and well-being of people in low- and middle-income countries by sustainably transforming animal and aquatic food systems. This will be achieved through six Areas of Work (AoW): Productivity+; Climate and Environment; One Health; Market Systems, Policy Solutions and Scaling; Gender, Youth, and Social Inclusion; and Digital and Data Solutions. The program operates in 17 countries globally, including Vietnam. In Vietnam, the program is implemented in Son La and Thai Nguyen provinces. It is coordinated by the International Livestock Research Institute (ILRI) and the International Center for Tropical Agriculture (CIAT), in close partnership with national and local stakeholders. Thai Nguyen province was a key site for CGIAR’s One Health Initiative (2022–2024), which is now transitioning into the SAAF program. This shift will incorporate additional SAAF AoW to better address local system challenges, particularly those associated with the pig value chain, recognized as a strategic species by local authorities during two rounds of consultations conducted by the project team. On 27–28 August 2025, ILRI and CIAT in partnership with Thai Nguyen University of Agriculture and Forestry (TUAF) and Thai Nguyen Sub-Department of Animal Health, Livestock and Fisheries (Sub-DAH) jointly coordinated a one and a half-day workshop. The workshop brought together 40 participants representing agriculture, health, environment, local authorities, veterinary services, and market actors (feed suppliers, farmers, cooperatives, traders, slaughterhouses). It focused on developing the theory of change (ToC) for SAAF in Vietnam, with a particular emphasis on the pig value chain in Thai Nguyen Province.